2014
DOI: 10.1186/1471-2431-14-86
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of childhood obesity and overweight in Bangladesh: findings from a countrywide epidemiological study

Abstract: BackgroundObesity has been declared an epidemic in many high income countries. In low income countries, the coexistence of obesity and underweight makes the situation more grievous. The priority is to explore the overall pictures of body weight status in low income countries and countries that are in transitional phase. Through this country wide cross sectional study we would like to capture the current body weight status among the school aged children, both in urban and rural areas in Bangladesh.MethodsWe con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
49
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 23 publications
4
49
1
Order By: Relevance
“…(Bangladesh Heart Journal 2016; 31 (2) : [80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97][98][99] The exact prevalence of CVD in Bangladesh is not known. Probably the first attempt to determine the prevalence of heart disease was made by Malik et al in a survey amongst 7062 people of different age groups in Dacca City and in a village; the surgery revealed the prevalence of 2.92%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(Bangladesh Heart Journal 2016; 31 (2) : [80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97][98][99] The exact prevalence of CVD in Bangladesh is not known. Probably the first attempt to determine the prevalence of heart disease was made by Malik et al in a survey amongst 7062 people of different age groups in Dacca City and in a village; the surgery revealed the prevalence of 2.92%.…”
Section: Methodsmentioning
confidence: 99%
“…A recent review showed an increasing trend in childhood obesity over time in Bangladesh; prevalence ranged from less than 1% to 17.9% based on different reference standards, with higher percentage amongst urban children. 84 In a recent countrywide cross sectional study, from June to September 2009 among 10,135 students of 6 to 15-year age group from both the urban and rural schools 85 , 3.5% were obese, 9.5% were overweight and 17.6% were underweight. The proportion of obese and overweight students were greater among the students from urban schools (5.6% and 10.6% respectively) compared to the students from rural schools (1.2% and 8.6% respectively) (Risk difference, RD = 4.3, 95% CI = 3.6, 5.0; RD = 2.0, 95% CI = 0.1, 3.1).…”
Section: Lifestyle Related Factorsmentioning
confidence: 99%
“…However, data for overweight and obesity prevalence among children in different countries in South Asia are available: 25.0% among children from 2 to 15 years in Bangladesh and 22.0% among children from 5 to 19 years in India. Moreover, secular trends indicate increasing prevalence rates in these countries: for example, 9.8 to 11.7% among children from 5 to 19 years in India during 2006-2009 [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…In general, 45 % of people of working age in Ukraine are obese. The latest investigation on epidemiology of alimentary obesity in Bangladesh indicate increasing of the incidence of this disease among school-age children in perspective will lead to the increasing in number of obese adults 5 . In Bangladesh, nearly 40 % of children < 5 years are suffering from malnutrition 6 .…”
mentioning
confidence: 99%